Novel insight into miRNA biology and its role in the pathogenesis of systemic lupus erythematosus - Luo, Baiwei; Zhou, Kaixia; Liufu, Yingcong; Huang, Xia; Zeng, Huiqiong; Zhang, Zhaoyang (Frontiers in Immunology, 2022)
MicroRNAs(miRNAs) have emerged as key regulators that control and influence gene expression as well as multiple biological processes depending on their potential binding sites in human-protein coding genes and other unconventional patterns, including coding for peptides, activating Toll-like receptors as a ligand, and other manners. Accumulating evidence has demonstrated that microRNA expression is tightly regulated during phases of development, differentiation, and effector functions of immune cells, immunological disorders of systemic lupus erythematosus (SLE). This review outlines the biogenesis of miRNAs and their unconventional functions as well as underlying cellular and molecular mechanisms. It then summarizes our current knowledge about how the biogenesis of miRNAs is regulated. Moreover, an overview was provided concerning the role of abnormal expression of miRNAs in lupus immune cells. In particular, we will shed some light on the recent advances in the role of miRNAs and exosome-derived miRNAs in immunological and epigenetic pathways in the pathogenesis of SLE.